Electrochemically self-cleanable carbon nanotube interlayered membrane for enhanced forward osmosis in wastewater treatment. Issue 3 (June 2022) - Wang, Yun-Jie; Huang, Liang; Fang, Zheng; Wang, Xue-Meng; Gao, Miao; Liu, Hou-Qi; Li, Wen-Wei; Huang, Tian-Yin
Abstract: Forward osmosis (FO) is considered as a promising alternative to pressure-driven membrane processes for wastewater treatment due to its relatively low-energy operation and better fouling resistance, but biofouling still occurs during long-time operation. The electrochemical cleaning strategy is effective for membrane fouling control, but has been seldom applied to FO processes so far due to unsatisfactory performance. Here, we fabricated a carbon nanotube-interlayered thin-film composite membrane with high electric conductivity, water permeability and self-cleaning ability to favor FO operation. By taking advantage of the electro-generated oxidative species in situ, especially the reactive chlorine species generated from locally-accumulated chlorine ions, the deposited bacterial cells and extracellular polymeric substances on membrane surface were efficiently removed to sustain the membrane operation. Applying 2.5 V voltage to the fouled membrane for 30 min restored 85% of its original water flux, and remained stable performance in three operating cycles. Overall, our work provides an efficient electrochemical cleaning strategy for FO membrane fouling control, which may further promote the application of FO wastewater treatment technologies. Graphical Abstract: ga1 Highlights: Conductive CNT-modified TFC forward osmosis membrane was fabricated. CNT-TFC membrane exhibited high electrochemical activity and stability. Reversely-diffused and locally-enriched Cl- was oxidized to generate free chlorine. Electrochemical cleaning of the membrane efficiently removed the biofoulants.